2019
DOI: 10.21467/ajgr.7.1.3-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity Difference on Lipid Content from Chaetoceros muelleri on Continuous Reactors

Abstract: Chaetoceros muelleri is a microalgae class of Bacillariophyta (diatom) which is generally only used as feeds for fishes and shellfish larvae. Nevertheless, the biochemical content of this species is quite high and has the potential to be developed. This research aims to explain the effect of different salinity on the growth and lipid content of Chaetoceros muelleri cultured in a continuous photobioreactor. This research was carried out in August 2018 - February 2019. The research was conducted at the Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…1g). The growth reduction was almost negligible at salinity 15, compared to 25 in a recent study using a continuous photobioreactor [Rahmadi et al 2020]. This tolerance to the wide range of salinity would be advantageous for bioremediation or nutrient recovery from the saline or brackish wastewater, which has been scarcely studied so far [Gengmao et al 2010].…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…1g). The growth reduction was almost negligible at salinity 15, compared to 25 in a recent study using a continuous photobioreactor [Rahmadi et al 2020]. This tolerance to the wide range of salinity would be advantageous for bioremediation or nutrient recovery from the saline or brackish wastewater, which has been scarcely studied so far [Gengmao et al 2010].…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, cultivating microalgae for obtaining not a single but multiple benefits simultaneously is receiving growing attention [ Chaetoceros muelleri is a marine diatom that is ubiquitously distributed worldwide. Because of its fast growth and easy maintenance, C. muelleri has been used in aquaculture as feed for zooplankton and shrimp larvae at commercial hatcheries in many regions [Wang et al 2014 Another reason that C. muelleri has been frequently used in aquaculture is its adaptation to salinity change [Fujii et al 1995;Barros et al 2014;Rahmadi et al 2020], which is likely to often occur in the land-based aquacultural ponds. Though the growth of Chaetoceros spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 200 L culture was carried out under controlled conditions in the Laboratory of Technologies for the Cultivation of Marine Organisms of the State University of Sonora using the “F” medium of Ryther and Guillard [ 10 ], white light illumination (3500 lux), 23 °C temperature, and continuous aeration. Daily cell counts were performed in triplicate using a Bright-line Neubauer hemacytometer with a 0.1-mm deep chamber, as previously described [ 8 ]. The biomass was flocculated with Al 2 (SO 4 ) 3 to facilitate the precipitation of the cells and harvested at the beginning of the stationary phase of the culture, established as the third day after inoculum (which was assigned as day 0).…”
Section: Methodsmentioning
confidence: 99%
“…The biomass of C. muelleri can generate high-value products, such as long-chain polyunsaturated fatty acids, proteins, and carbohydrates, making it one of the most important species of microalgae in the aquaculture industry. Several studies have been reported on the production of fatty acids and reserve carbohydrates in this species [ 8 ]. However, to date, there is no information on its sulfated polysaccharides.…”
Section: Introductionmentioning
confidence: 99%